Polycystic ovary syndrome treatment in the infertile woman. Notes on the recent thessaloniki Consensus. - Pacheco Romero, José (2015)
We summarize Thessaloniki Consensus’ conclusions for infertile women with polycystic ovary syndrome (PCOS) that wish to become pregnant. The Consensus indicates that first all other health problems and male infertility have to be excluded, and then continue with preconceptional counseling on life style, advising on lowering weight and exercise in overweight women, and discontinuing smoking and alcohol consumption. Recommended first line treatment for ovulation induction is still the antiestrogen clomiphene citrate. When clomiphene fails, second line treatment consists in using exogenous gonadotropins or laparoscopic ovarian diathermia. The third line of treatment is in vitro fertilization – FIV. GnRh antagonists use may lower the incidence of ovary hyperestimulation syndrome. Single embryo transference in (young) women with PCOS subjected to FIV is expected to correlate with the possibility of less multiple pregnancy. Other ovulation induction treatments adjusted to each PCOS patient are expected to be developed. Metformin use in PCOS for ovulation induction is not currently recommended and there is insufficient evidence to recommend aromatase inhibitors use in ovulation induction. Even single fetuses pregnancies in PCOS are associated with mother and fetus health risks.